COMPETENCE OF ENGLISH TEACHERS AT MADRASAH ALIYAH NEGERI (MAN) IN EAST KALIMANTAN - Bahrani, Bahrani; Ananiah, Ananiah; Aisyah, Siti; Taqim, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Good teacher competence will affect teacher performance and teacher professionalism; with competence possessed, a teacher will be able to master the material and be able to convey the material well, and quickly understand students. This study aims to determine the competence of English teachers at State Madrasah Aliyah (MAN) in East Kalimantan. The total population in this study was 21 people as a sample using purposive sampling. The instrument was a questionnaire then analyzed through the formula mean and percentage. Based on the results of statistical tests and discussion, the researchers concluded that the competence of English teachers at the State Aliyah Madrasah (MAN) in East Kalimantan was excellent, with an average score of 4.5. The average result for each competency, namely; spiritual competence (4.8), personal competence (4.8), social competence (4.7), professional competence and academic competence (4.5), while the average value of leadership competence is only 3.8 so that the leadership competence of MAN English teachers in East Kalimantan can be categorized Good. Keywords: Teacher Competency, English Teacher, Madrasah Aliyah Negeri